Effects of temperature, shear rate and constituents on rheological properties of tahin (sesame paste) - Lokumcu Altay, Filiz; Ak, M Mehmet (Wiley, 2004)
AbstractIn this paper, rheological properties of tahin are reported at temperatures from 20 to 70 °C and shear rates in the range 0.13–500 s−1. Temporary hysteresis loops were observed in the first cycle of the flow curves. The steady shear behaviour of tahin was pseudoplastic and described by a power law model. The consistency coefficient exhibited strong temperature dependence for which the activation energy of flow was 21.6 kJ mol−1. The flow behaviour index of tahin tended to increase whereas the consistency coefficient tended to decrease during storage at room temperature. Tahin oil exhibited Newtonian behaviour with a strong dependence of viscosity on temperature. The activation energy of flow for tahin oil was 35.7 kJ mol−1. While reconstituted suspensions containing up to 20% solids exhibited Newtonian behaviour, those with more solids and the original tahin showed pseudoplastic behaviour. The Krieger–Dougherty model fitted the suspension viscosity data well. Below 20% solids level there was no effect of particle size on the viscosity of the reconstituted suspensions. It was shown that for the same amount of solids the viscosity of a ‘polydisperse’ suspension was lower than that of a ‘monodisperse’ suspension. Copyright © 2004 Society of Chemical Industry